(3CSGSjGJ HMhK GdYedjGJs - (3CMeO eMeO GdgRGY(B, (3GdUeGOjs ((3YeGf(B:s (3OGQ bfOjd ddfTQ(B,s, 2008)
(3jJfGhd GdcGJH ebOeI aj HMhJ GdYedjGJ hGdHQeLI GdNWjI JYQja GdHQeLI GdNWjI hcjajI HfGA GdfehOL GdQjGVj ceG JWQb Gdj GdJMdjd GdMSj hGdfehOL GdebGHd GdJMdjd GdMSj hGdMOhO GdOfjG hGdbUhj dOGdI GdgOa cOGdc eTGcd Gdfbd Gdeaghe GdYGe deTGcd Gdfbd WQb GjLGO GdMd GdGHJOGFj deTGcd Gdfbd heTGcd GdJYjjf ef Gdeaghe GdYGe deTGcd GdJYjjf hWQb Md eTGcd GdJYjjfGjVG GdJMdjd GdTHcj GgejI GdJMdjd GdTHcj eaGgje GSGSjI aj GdJMdjd GdTHcj hMdhd HYV GdGSFdI (B.(3edMb (B.(3GSFdI GeJMGf TGeds
(3HjHdjhZQGajG(B: (3U(B.276s
Keywords: (3EOGQI GdCYeGds; (3HMhK GdYedjGJs